The Analysis of Functional Needs on Undergraduate Thesis Information System Management: A Case Study in Indonesian Universities - Lila Setiyani; Abin Syamsudin; Abdorrakhman Gintings; Daeng Arifin (Indonesian Scientific Journal, 2020)
Undergraduate thesis is a scientific paper that students must complete to get a bachelor’s degree. During the completion of the thesis, many students face difficulties in determining research topics, supervision, and administration processes so that they cannot graduate on time. This study aims to analyze the functional needs of the undergraduate thesis information system management that is needed by both students and administrators. This system serves to accelerate the thesis preparation process that is useful for students, supervisors, and thesis administration managers. The procedure of the study was conducted by compiling matrix planning and data collection. As the data source, this study involved 20 students who were writing their undergraduate thesis and 10 alumni who have completed their theses. This sample was selected with the criteria of students or alumni who have been involved in the undergarduate thesis business process. In the process of taking samples reseachers used a purposive sampling method. In addition, difficulties in managing the thesis were also explored by supervisors and study program management. Furthermore, the data were analyzed through PIECES (Performance, Information, Economy, Control, Efficiency, Service). This study produces a list of functional needs on the thesis management system that can encourage students to graduate on time, in which universities can implement this system and socialize it to users.